Registered Replication Report on Fischer, Castel, Dodd, and Pratt (2003). Issue 2 (June 2020) - Colling, Lincoln J.; Szűcs, Dénes; De Marco, Damiano; Cipora, Krzysztof; Ulrich, Rolf; Nuerk, Hans-Christoph; Soltanlou, Mojtaba; Bryce, Donna; Chen, Sau-Chin; Schroeder, Philipp Alexander; Henare, Dion T.; Chrystall, Christine K.; et al.
The attentional spatial-numerical association of response codes (Att-SNARC) effect (Fischer, Castel, Dodd, & Pratt, 2003)—the finding that participants are quicker to detect left-side targets when the targets are preceded by small numbers and quicker to detect right-side targets when they are preceded by large numbers—has been used as evidence for embodied number representations and to support strong claims about the link between number and space (e.g., a mental number line). We attempted to replicate Experiment 2 of Fischer et al. by collecting data from 1, 105 participants at 17 labs. Across all 1, 105 participants and four interstimulus-interval conditions, the proportion of times the effect we observed was positive (i.e., directionally consistent with the original effect) was .50. Further, the effects we observed both within and across labs were minuscule and incompatible with those observed by Fischer et al. Given this, we conclude that we failed to replicate the effect reported by Fischer et al. In addition, our analysis of several participant-level moderators (finger-counting habits, reading and writing direction, handedness, and mathematics fluency and mathematics anxiety) revealed no substantial moderating effects. Our results indicate that the Att-SNARC effect cannot be used as evidence to support strong claims about the link between number and space.